2008
DOI: 10.1002/chem.200801273
|View full text |Cite
|
Sign up to set email alerts
|

N,N‐Dimethylaminopropylsilane: A Case Study on the Nature of Weak Intramolecular Si⋅⋅⋅N Interactions

Abstract: N,N-Dimethylaminopropylsilane H(3)Si(CH(2))(3)NMe(2) was synthesised by the reaction of (MeO)(3)Si(CH(2))(3)NMe(2) with lithium aluminium hydride. Its solid-state structure was determined by X-ray diffraction, which revealed a five-membered ring with an SiN distance of 2.712(2) A. Investigation of the structure by gas-phase electron diffraction (GED), ab initio and density functional calculations and IR spectroscopy revealed that the situation in the gas phase is more complicated, with at least four conformers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 54 publications
3
38
0
3
Order By: Relevance
“…Such effects are known to be overemphasized by MP2, but are described more balanced by SCS-MP2 [25] The situation in 2 is completely analogous to the bonding situation observed in N,N-dimethylaminopropylsilanes for the weak intramolecular Si-N interactions [26]. The main driving force for the complex formation can be assigned to electrostatic interactions.…”
Section: Resultsmentioning
confidence: 97%
“…Such effects are known to be overemphasized by MP2, but are described more balanced by SCS-MP2 [25] The situation in 2 is completely analogous to the bonding situation observed in N,N-dimethylaminopropylsilanes for the weak intramolecular Si-N interactions [26]. The main driving force for the complex formation can be assigned to electrostatic interactions.…”
Section: Resultsmentioning
confidence: 97%
“…[154] Open and cyclic conformers of N,N-dimethylaminopropylsilane (Scheme 4) were exhaustively characterized in the gas phase,i ns olution, and in the solid state. [156] In the crystalline state,t he molecule exists solely in the cyclic form with aw eak dative bond, while it displays ad ynamic equilibrium in the gas phase with at least three open conformers and ac yclic one.T he SiÀNb ond length (r), for which ab ond critical point was located, is 2.91 , as determined by gas-phase electron diffraction (GED). Computations at several levels of theory indicate that r Si-N crucially depends on the treatment of electron correlation and exhibits as catter from 3.14 ( HF) to 2.73 ( MP2).…”
Section: Methodsmentioning
confidence: 99%
“…On paper, TCMA shares structural similarities with tris(2-chloroethyl)amine, N(CH2CH2Cl)3, a powerful military-grade blister agent associated with acute cytotoxicity [31][32][33][34], but on the basis of the work by Oberhammer et al [18][19][20][21][22][23][24][25], the three-dimensional geometry around the amide centre should be anticipated to be quite different. Indeed, the structural solution in the gas phase from GED may be anticipated to be quite different to that obtained for the single crystal using XRD, as work by Mitzel et al [35][36][37][38][39] has demonstrated.…”
Section: Introductionmentioning
confidence: 93%